MOET Efficiency in a Spanish Herd of Japanese Black Heifers and Analysis of Environmental and Metabolic Determinants - Vázquez-Mosquera, Juan M.; Fernández-Novo, Aitor; Bonet-Bo, Martin; Pérez-Villalobos, Natividad; Pesántez-Pacheco, Jose L.; Pérez-Solana, Maria L.; De-Mercado, Eduardo; Gardón, Juan C.; Villagrá, Arantxa; Sebastián, Francisco; Pérez-Garnelo, Sonia S.; Martínez, Daniel; et al. (MDPI, 2022)
Multiple ovulation and embryo transfer (MOET) systems have been intensively implemented in Japanese Black cattle in Japan and to create Japanese Black herds out of these areas. Environmental conditions influence MOET efficiency. Thus, we describe results of 137 in vivo, non-surgical embryo flushings performed between 2016–2020, in a full-blood Japanese Black herd kept in Spain and the possible effects of heat, year, bull, donor genetic value, and metabolic condition. Additionally, 687 embryo transfers were studied for conception rate (CR) and recipient related factors. A total of 71.3% of viable embryos (724/1015) were obtained (5.3 ± 4.34/flushing). Donor metabolites did not affect embryo production (p > 0.1), although metabolite differences were observed over the years, and by flushing order, probably related to the donor age. CR was not affected by embryo type (fresh vs. frozen), recipient breed, and whether suckling or not suckling (p > 0.1). CR decreased significantly with heat (44.3 vs. 49.2%; (p = 0.042)) and numerically increased with recipient parity and ET-number. Pregnant recipients showed significantly higher levels of cholesterol-related metabolites, glucose, and urea (p < 0.05). Therefore, adequate MOET efficiency can be achieved under these conditions, and heat stress should be strongly avoided during Japanese Black embryo transfers. Moreover, recipients’ metabolites are important to achieve pregnancy, being probably related to better nutrient availability during pregnancy.